Seascapes - Sekular, Tomasz (Taideyliopiston Kuvataideakatemia, 2024)
The artistic component of my master thesis project comprises of a single channel moving image installation, exhibited at Hyvinkää town museum’s Taika center between 1.11.2023- 7.1.2023, as part of the Boisterous light-exhibition. The installation is formally a natural evolution of my artistic practice as it touches upon a number of my interests in the field of contemporary art and its manifestation in the moving image and screen-based practices: Materiality, Perception, Movement, Representation and the apparatus. The formal and material elements in the installation include water, mist, hydroponic humidifiers, an acrylic tank, programmed pc-fans, a video loop, back projected with an accompanying stereo soundscape. The work seeks to push and expand the moving image into an hybrid realm, considering the representation of the sea, the experiential and intermediate elements in art making and in this particular case, common points of departure for Painting, light art and the moving image, and most importantly producing a work and aesthetic encounter that contemplates on the corporeality and tactility of vision. Another essential factor in my artistic component is derived from a consideration of the transmission and mediation of images, both mental and external in contemporary society. The written component will consist of reflections and meditations on past projects that led me on to my current path, influential texts and scholars that have indirectly opened up avenues for personal growth and questions regarding my practice as a visual artist. I will explicate and reflect on my artistic process with regard to two installations and seek to contextualise the works within a wide framework of references from multiple fields of study. Hopefully illuminating the reader on the themes and interests prevalent in my works. I will reference the writings of Giuliana Bruno with projection and the surface tension in media and moving image, Gilles Deleuze’s aesthetics on the logic of sensation and Margaret Morse on moving image installations, as they relate to my disposition toward the moving image and occasionally coherent thoughts about art-making more widely, amidst other scholars and practicioners predominantly interested in the moving image and cinema. Moreover, I will go into the working process in separate chapters, comparing the two installations with each other.
Keywords: installaatiot; tilataide; taidenäyttelyt; nykytaide; kuvataide; fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|